Lice infestation in goats in western Santa Catarina, Brazil - Albani K.D.* (2014)
Parasitic diseases affecting goats are able to cause major economic losses, standing out, among them, the lice infestation. According to the literature, lice can act as vectors of other diseases, including the ones caused by blood protozoan. In this sense, this survey study aimed to assess the ectoparasites of goats in the west region of Santa Catarina (SC). Two hundred seventeen goats from 24 different rural properties located in 17 towns in SC were examined. From them, ectoparasites were collected and evaluated in laboratory, where the parasitological classification was performed. In 13 properties, it was possible to identify ectoparasites. Damalinia caprae lice were observed in 126 animals (58 %), while Linognathus stenopsis were found in 10 animals (4.6 %). It is noteworthy that, in these properties, all the animals were under lice parasitism, independent of sex or age. The goats had peeling skin, particularly in the back region (lumbar). All of the 24 properties evaluated were reported having problems with lice in different seasons of the year, even under regular treatment with cypermethrin (spraying). Based on our findings, it was possible to conclude that D. caprae is the major ectoparasite of goats in the investigated area. © 2013 Springer-Verlag London.